Factors associated with, issues related to, and suggestions for increasing participation in workplace health promotion programs. - Wilson MG (Health Values: The Journal of Health Behavior, Education & Promotion)
This review examines factors associated with, issues related to, and suggestions for increasing participation in workplace health promotion programs. The purpose is to help health professionals better understand why people participate and how program planners can effect participation. The lack of results and contradictory findings of some studies emphasize the complex nature of participation. Studies have shown that participants are likely to be young with high education and income. Preliminary studies have also shown a relationship between participation and some behavioral and psychosocial variables, although these studies have yet to be confirmed. The participation issues of self-selection and comprehensiveness are discussed. Suggestions for increasing participation are offered.